2023
DOI: 10.1021/acsnano.2c10127
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Soft Robot for Minimally Invasive Urethral Catheter Biofilm Eradication

Polina I. Baburova,
Daniil V. Kladko,
Alina Lokteva
et al.

Abstract: Catheter-related biofilm infection remains the main problem for millions of people annually, affecting morbidity, mortality, and quality of life. Despite the recent advances in the prevention of biofilm formation, alternative methods for biofilm prevention or eradication still should be found to avoid traumatic and expensive removal or catheter replacement. Soft magnetic robots have drawn significant interest in favor of remote control, fast response, and wide space for design. In this work, we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…These include the biocompatibility of neodymium-iron-boron in applications [ 25 ] and clinical efficacy issues like biofilm infections in hydrogel thin films. Although these issues have garnered the attention of biomedical researchers [ 192 ], challenges remain regarding such technologies’ mechanisms and effective control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the biocompatibility of neodymium-iron-boron in applications [ 25 ] and clinical efficacy issues like biofilm infections in hydrogel thin films. Although these issues have garnered the attention of biomedical researchers [ 192 ], challenges remain regarding such technologies’ mechanisms and effective control.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, in actual surgical applications, it is necessary to consider problems faced by interdisciplinary, such as biofilms [ 189 ] and infections related to catheters [ 190 , 191 ]. Although the literature [ 192 ] proposes a strategy for preventing biological infections, it still confronts multiple challenges [ 193 ]. Therefore, realizing the application of magnetic soft robots in the medical field requires interdisciplinary collaboration and integration.…”
Section: Magnetic Soft Robotsmentioning
confidence: 99%
“…Specifically, together with wide surface coverage and deep penetration through narrow cavities, the swarming Fe 3 O 4 @PDA-TA NRs not only can rapidly eradicate bacteria residing on the superficial infection site through localized photothermal ablation but also exert sustained antibacterial action in the deep infection site through their inherent chemical activities. In contrast, those magnetic MNRs relying on single-mode physical (e.g., mechanical force and photothermal hyperthermia) or chemical antibacterial strategy (e.g., antibiotic drugs and ROS/nitric oxide generation) usually suffer from limited applicability or low bacterial elimination efficiency [ 43 , 62 64 ]. While some studies have reported MNRs integrating physical and chemical sterilization, they typically involve large microrobots (tens of micrometers) with catalytic properties or loaded antibiotics [ 42 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms can cause many diseases, such as periodontitis [ 3 ], otitis media [ 4 , 5 ], osteomyelitis [ 6 , 7 ]. Furthermore, it should be noted that biofilms have the capability to adhere to various materials, including catheters [ 8 , 9 , 10 ], prosthetic joints [ 7 , 11 ], contact lenses [ 12 ], mechanical artificial heart valves [ 13 ], and others. This attachment often leads to the development of infections in these materials.…”
Section: Introductionmentioning
confidence: 99%